Pengembangan Kota Wisata Syariah dengan Peningkatan UMKM Syariah - Soraya Lestari; Novi Hardiyanti (Universitas Proklamasi 45 Yogyakarta, 2019)
The growth of the Islamic economy is currently growing rapidly. This can be seen from the number of Micro, Small, and Medium Enterprises (MSMEs) that adopt the principles of Islamic business. Sharia MSME is a means of creating jobs and encouraging economic progresses, and advancing private sector businesses. The emergence of many new entrepreneurs who adopted the sharia system in Aceh becomes a great opportunity as a center for sharia products. Not only sharia products, Sharia MSMEs more broadly include the application of the Islamic financial system, including culture, entertainment, lifestyle, and tourism. The need for Aceh's flagship products wrapped in nuances of Islamic principles is still very limited in Aceh. It becomes an obstacle to make Aceh as a tourist destination with Islamic principles. The number of embroidery craftsmen is still less compared to the number of requests. This condition is based on the work that is still traditional and has not used a computerized machine yet. The limitations of human resource capabilities often become obstacles for using technology, production processes, and business development. The increase in sharia tourism will have a positive impact on the improvement of sharia MSMEs. This can be seen from the level of creativity, knowledge, and marketing according to tourist demand. The purpose of this study was to determine whether there is a significant influence of creativity, knowledge, and marketing to the improvement of Islamic MSMEs. This research has been conducted with questionnaires for the entrepreneurs’ MSMEs of embroidery products in Aceh. The results of this study indicate that createvity, knowledge, and marketing simultaneously influence the improvement of sharia MSMEs. Partially, creativity and knowledge variables do not influence the improvement of sharia MSMEs, while marketing affects the improvement of sharia MSMEs significantly.